Postsecular Lessons: Performing Psychology Differently. (February 2014) - Brinkmann, Svend
Psychology has been modernity's most influential social science intervention, shaping the self-understanding of human beings in countless ways. The "everywhereness of psychology" is comparable with the role of religion in premodern times. Today, however, the world seems to go through a process of postsecularism, and the author uses this as an occasion to stage a confrontation between psychology and religion/spirituality, played out concretely and autobiographically as a meeting between the psychologist-researcher and his friend with whom he lost contact almost 10 years ago, when the friend joined a spiritual community. The text both recounts an attempt made by the secularist psychologist-researcher to understand religion and spirituality, but also experiments with performing psychology differently.